Adopsi Inovasi End-User Computing Satisfaction dan Importance Performance Analysis Untuk Mengukur Tingkat Kepuasan Pengguna eKatalog di Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah - Muhammad Ridwan Ravly Hendy Prayoga (Journal of Research in Industrial Engineering and Management, 2026)
Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah (LKPP) is a non-ministerial government agency directly responsible to the President of the Republic of Indonesia. In general, LKPP is tasked with formulating policies and regulations for government goods/services procurement, providing technical guidance and advocacy related to the implementation of government goods/services procurement, and facilitating the implementation of government goods/services procurement expert certification exams. This research begins with the problems directly experienced by e-catalog users, then a few studies that apply the EUCS method to the population of e-catalog users. Therefore, it is necessary to conduct research to measure the level of user satisfaction which aims to determine the level of satisfaction of e-catalog users. The author uses the End-User Computing Satisfaction (EUCS) method which consists of 5 (five) main variables, namely content, accuracy, format, timeliness, ease of use, then the author adds 1 (one) variable based on existing problems, namely the support system variable. The author performs data analysis techniques using SEM-PLS. The results of the EUCS method get an R-Square value of 0,726 which means the level of user satisfaction is in the moderate category. Then there are 3 (four) variables that have a significant effect, namely accuracy, content, format, and there are 3 (two) variables that do not have a significant effect, namely ease of use, support system, timeliness.